2013
DOI: 10.1159/000346743
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Time Trends in Etiology of Hepatocellular Cancer in Germany

Abstract: Introduction: The incidence of hepatocellular cancer (HCC) continues to rise in Europe with a shift of the primary cause towards alcoholic and non-alcoholic fatty liver disease. Metabolic factors like diabetes mellitus and overweight have been identified as significant risk factors for HCC development. Patients and Methods: A retrospective analysis in a large single-center cohort of 650 patients diagnosed with HCC was performed. Demographic characteristics, risk factors, tumor stage at diagnosis and survival w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 86 publications
3
21
1
1
Order By: Relevance
“…The prevalence of HCC-NC in this Brazilian study was elevated (16%), and the results were similar to those found in other studies conducted in Western countries [6][7][8] . The patients were most frequently of advanced ages (mean of 64.4 years) and predominately male.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The prevalence of HCC-NC in this Brazilian study was elevated (16%), and the results were similar to those found in other studies conducted in Western countries [6][7][8] . The patients were most frequently of advanced ages (mean of 64.4 years) and predominately male.…”
Section: Discussionsupporting
confidence: 91%
“…In Western countries, the prevalence of hepatocellular carcinoma in non-cirrhosis (HCC-NC) patients was estimated in 15% to 20% of cases [6][7][8] , and the most common risk factors were HBV and HCV. However, a majority of the information was obtained from Asia and Africa, where the prevalence of hepatitis B and C viral infections is also elevated [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of transplants from the ELTR demonstrated that NAFLD may be under-recognized as an indicator for liver transplant, with many transplants classified simply as cirrhosis or HCC [36]. Studies of transplant recipients in Sweden and Germany report that over 40% of cases classified as cryptogenic cirrhosis were NASH-related [37] and NASH was the third leading cause of HCC resulting in transplantation [38]. In the US, there is evidence that numerous transplants indicated for cryptogenic or idiopathic cirrhosis are NAFLD-related based on obesity rates in this population [39,40].…”
Section: New Nafld Casesmentioning
confidence: 99%
“…The liver is the central organ involved in the metabolism of nutrients, and in patients with liver cirrhosis malnutrition is a common attribute and associated with mortality and reduced quality of life [5]. In case of HCC, that in the majority of cases is associated with liver cirrhosis [6,7], tumor progression and tumor directed therapies can directly impact on liver function additionally [8].…”
Section: Introductionmentioning
confidence: 99%